Aspiration Pneumonitis Caused by Polyethylene Glycol-Electrolyte Solution Treated with Conservative Management. (18th May 2014) - Mosquera, Ricardo A.; McDonald, Mark; Samuels, Cheryl
Abstract : Polyethylene glycol (PEG) electrolyte solution, Golytely, is an osmotic laxative commonly used in preoperative bowel cleansing. In this case report, a 9-year-old boy developed aspiration pneumonitis following accidental infusion of PEG solution into his right lung following migration of his nasogastric tube (NGT). Hypoxemia and tachypnea without respiratory failure were observed after infusion. Because PEG is a nonabsorbable toxic material, previous case reports have advocated for the performance of bronchoalveolar lavage (BAL) in the treatment of PEG pneumonitis. With close monitoring, our patient was able to be successfully treated without the need for invasive interventions including BAL or intubation. Generalizations about PEG absorption in the lung based on its permeability in the gastrointestinal tract should not deter the use of more conservative treatment in the appropriate patient.